2021
DOI: 10.6061/clinics/2021/e1816
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of abdominal ultrasound inspection in the diagnosis and prognosis of neonatal necrotizing enterocolitis

Abstract: OBJECTIVE: This study aimed to identify the most useful ultrasound (US) features associated with definite neonatal necrotizing enterocolitis (NEC) and their prognostic values, particularly the calculated markers combined with important features. METHODS: A total of 213 suspected NEC cases were collected from the neonatal department of our hospital from January 2015 to August 2017. Each infant received both X-ray and US examinations. RESULTS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Feingold et al [ 23 ] measured the intestinal wall thickness of 30 children without gastrointestinal diseases, 22 children with NEC and 8 children with suspected NEC and found that the intestinal wall of children with NEC was thickened or thinned to varying degrees, among which the intestinal wall of 8 children with severe NEC was thinned, and the follow-up found that all 8 children had intestinal necrosis. This study confirmed that the course of NEC is accompanied by a change in intestinal wall thickness, and the intestinal wall thickness in the early stage of NEC displays nonuniform thickening [ 24 , 25 ]. This finding is consistent with the results of the present study showing that the intestinal wall thickness of infants with stage I and II NEC is thicker than that of infants with bowel loss.…”
Section: Discussionsupporting
confidence: 76%
“…Feingold et al [ 23 ] measured the intestinal wall thickness of 30 children without gastrointestinal diseases, 22 children with NEC and 8 children with suspected NEC and found that the intestinal wall of children with NEC was thickened or thinned to varying degrees, among which the intestinal wall of 8 children with severe NEC was thinned, and the follow-up found that all 8 children had intestinal necrosis. This study confirmed that the course of NEC is accompanied by a change in intestinal wall thickness, and the intestinal wall thickness in the early stage of NEC displays nonuniform thickening [ 24 , 25 ]. This finding is consistent with the results of the present study showing that the intestinal wall thickness of infants with stage I and II NEC is thicker than that of infants with bowel loss.…”
Section: Discussionsupporting
confidence: 76%
“…Key AUS features of NEC were observed carefully (Tam et al, 2002 ; Faingold et al, 2005 ; Epelman et al, 2007 ; Silva et al, 2007 ; Muchantef et al, 2013 ; Patel et al, 2015 ; Allin et al, 2017 ; Erinumberger, 2017 ; Chen et al, 2018 ; Faingold, 2018 ; Markel and Underwood, 2018 ; Ben Fadel et al, 2019 ; van Druten et al, 2019 ; Miller et al, 2020 ; Tracy et al, 2020 ; Alexander et al, 2021 ; Chan et al, 2021 ; Gao et al, 2021 ; Kotb et al, 2021 ; Cuna et al, 2022 ; Hwang et al, 2022 ). These features included (1) bowel wall thickness: normal between 1 and 2–2.7 mm; (2) decreased intestinal peristalsis: intestinal peristalsis <10 times/min.…”
Section: Methodsmentioning
confidence: 99%
“…These features included (1) bowel wall thickness: normal between 1 and 2–2.7 mm; (2) decreased intestinal peristalsis: intestinal peristalsis <10 times/min. (3) Pneumatosis intestinalis (PI): granular, stripe, ring-shaped hyperechoic foci in the intestinal wall; (4) portal venous gas (PVG): movable granular hyperechoic foci within the portal vein and its branches; (5) pneumoperitoneum: free intraperitoneal air seen as echogenic foci or stacked echogenic lines outside the bowel lumen; (6) ascites: detectable free liquid dark areas in the abdominal cavity (simple free fluid was seen as anechoic regions surrounding intraperitoneal structures, while complex free fluid was seen as echogenic, with possible loculations); and (7) bowel perfusion: increased perfusion with >9 dots of color Doppler signal per square centimeter (Alexander et al, 2021 ; Gao et al, 2021 ). The key AR features of NEC included PVG, pneumoperitoneum, bowel dilatation, and reduced inflation (van Druten et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%